2016
DOI: 10.1103/physrevb.94.125436
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption geometry and interface states: Relaxed and compressed phases of NTCDA/Ag(111)

Abstract: The theoretical modelling of metal-organic interfaces represents a formidable challenge, especially in consideration of the delicate balance of various interaction mechanisms and the large size of involved molecular species. In the present study, the energies of interface states, which are known to display a high sensitivity to the adsorption geometry and electronic structure of the deposited molecular species, have been used to test the suitability and reliability of current theoretical approaches. Two well-o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
(105 reference statements)
0
14
0
Order By: Relevance
“…59,60 This interpretation was subsequently confirmed by density-functional theory (DFT) calculations. [61][62][63][64][65][66] In the meantime, additional molecules, e.g., NTCDA, 63 H 2 Pc and FePc 48 grown on Ag(111) and other substrates have been investigated, [67][68][69][70][71][72][73][74][75][76][77][78][79] which confirm the rather general phenomenon of the existence of interface states. Such a state can be successfully described by a model potential combining the metal substrate and a flat π-conjugated molecular layer.…”
Section: Tiopc-ag Interface Statementioning
confidence: 59%
“…59,60 This interpretation was subsequently confirmed by density-functional theory (DFT) calculations. [61][62][63][64][65][66] In the meantime, additional molecules, e.g., NTCDA, 63 H 2 Pc and FePc 48 grown on Ag(111) and other substrates have been investigated, [67][68][69][70][71][72][73][74][75][76][77][78][79] which confirm the rather general phenomenon of the existence of interface states. Such a state can be successfully described by a model potential combining the metal substrate and a flat π-conjugated molecular layer.…”
Section: Tiopc-ag Interface Statementioning
confidence: 59%
“…Timeand angle-resolved two-photon photoemission (2PPE) experiments on PTCDA/Ag(111) concluded from the dispersion and the rather short inelastic lifetime of this state that it must originate from the Shockley surface state of the bare Ag(111) substrate which is upshifted from below the metallic Fermi level by as much as 0.7 eV due to the interaction with the molecular layer [5,21]. This interpretation was subsequently confirmed by density-functional theory (DFT) calculations [6,[22][23][24][25][26], which showed that the hybridization of molecular and metallic states is rather small in the region of the projected band gap of the metal.…”
Section: Introductionmentioning
confidence: 85%
“…Both make such calculations very time-consuming. Moreover, metal-organic interfaces require tailored calculations methods 26 , because conventional DFT neither correctly accounts for van der Waals forces which have an important contribution to the interaction between organic molecules and metal surfaces nor for the correct long-range interaction in front of metal surfaces.…”
mentioning
confidence: 99%
“…Monolayers of PTCDA molecules on various silver surfaces have been extensively examined using a wide range of experimental techniques. 6,7 Thus, a detailed description of adsorption geometry [8][9][10][11][12] and electronic structure is available in the literature [13][14][15][16][17] . Density functional theory (DFT) was repeatedly applied for a successful description of PTCDA/Ag(111) as well 5,[18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%